The Influence of Political Advertisements on Television on the Level of Political Trust of the People of Yogyakarta City - Muhammad Ismail Alfan Zamzami; Gibbran Prathisara (Jogjakarta Communication Conference (JCC), 2024)
People's political participation is not only influenced by internal factors such as knowledge and awareness of rights and obligations related to the social environment and political activity, but also by political beliefs which are important determinants. One media that has a significant role in shaping political beliefs is television. Since its inception, television has proven to be one of the main sources of political information for the public. Therefore, this study aims to investigate the influence of political advertisements delivered through television on the level of political trust of the people in Yogyakarta City. This study adopts the theory of Mass Media Effects, specifically the Theory of Moderate Effects, which emphasizes that the influence of mass media can vary depending on the characteristics of the individuals who receive the message of the media. By locating this research in Yogyakarta City and involving 50 respondents as a sample, this study used a descriptive quantitative approach. Data were collected through questionnaires or questionnaires and analyzed using simple linear regression analysis methods as well as coefficient of determination analysis. From this study, it was found that there was an influence between political advertisements on television on the political beliefs of the people of Yogyakarta City which was blinded with a Tcount value of 17.844 > a Ttable value of 2.008, and from a significant value of 0.000 < 0.05. Furthermore, the magnitude of the influence of political advertisements on television on the political trust of the people of Yogyakarta City can be seen from the adjusted R square value of 0.020, which means that the magnitude of the influence of political advertisements on television on the political trust of the people of Yogyakarta City is only 2%.